PEMBERDAYAAN TP. PKK BERBASIS KELOMPOK DASAWISMA DALAM MENINGKATKAN EKONOMI KREATIF DI DESA TEPAS KECAMATAN BRANG REA KABUPATEN SUMBAWA BARAT - Junaidi Efendi; Sopan Hidayat; Silvan Kasrah; Rukaiyah; Yayan Priyantono; Dwi Ariyani; Aliya Sita Nirmala; Sumarni; Muhammad Faqih Bafadal; Idwin Has Saputra; Bahtiar Nopandi; Fani Sastra Pranata; et al. (Jurnal Wicara Desa, 2023)
The creative economic empowerment proclaimed in the Cordova University thematic KKN work program in Tepas Village in collaboration with the PKK Tepas Berjaya further emphasizes strengthening the empowerment of housewives who are members of the Dasawisma group in the Moringa menu creation program and saving used cooking oil which is considered to be able to overcome household waste problems and can improve the economy and family welfare towards an independent village. The empowerment of women through Dasawisma has been carried out by the PKK in Tepas village since 2020, this is a form of PKK's concern and sensitivity for housewives who have been affected by the covid-19 pandemic. In its activities Dasawisma members are empowered to have skills in processing Moringa vegetables into several menus such as snacks or souvenirs and which have economic value which will later be marketed through online or offline markets. or delivered by the women of the Tepas village community to be saved in the form of money or exchanged for new cooking oil. The Tepas Village PKK plans to create 40 (forty) processed moringa menus that are ready to be marketed as well as an increase in the community to actively participate in these waste-consuming savings activities. The current problem is that the achievements of processed moringa are still far from the targets set out of the PKK in Tepas village program and used cooking oil has not yet been processed into goods of economic value, so based on this, Cordova University thematic KKN students initiated several menus of processed food/snacks and souvenirs from processing of moringa and utilization of used cooking oil to become souvenirs. Limited understanding of creativity, entrepreneurship and limited knowledge and care in the midst of society is also the basis for this service to be carried out. Activities carried out include counseling, initiation of new products, entrepreneurship assistance, collaboration and continued with joint practice. The result of this service activity is that Dasawisma members have knowledge about processing used cooking oil into goods of economic value such as liquid soap and aromatherapy candles and add to the processed moringa menu in the form of snacks and souvenirs in the form of kelor ecoprint, then increase the knowledge of Dasawisma members about entrepreneurship